Antiparkinsonian for Treatment of Neurological Sequels Caused by Canine Distemper: Antiparkinsoniano para tratamento de sequelas neurológicas causadas pela cinomose - Almeida Oliveira, Mariana; Henrique Ronchi, Pedro; Henrique Dufloth Gutschow, Gabriel; Andrei Martinez-Pereira, Malcon (Acta Scientiae Veterinariae, 2023)
Background: Canine distemper (CD) is a highly contagious viral disease caused by the canine distemper virus (CDV). In dogs, CDV infection is characterized by the presentation of systemic and/or neurological signs with viral persistence in some organs, including the central nervous system (CNS). Neurological damages resulting from CD are a defiance for veterinarians, due to occasioned clinical sequels that influence the patient quality of life. The treatment of sequelae should seek to promote the resolution or decrease of the deleterious effects that impede the patient independence. Thus, the present report aims to describe the action of antiparkinsonian medication (levodopa associated with carbidopa) administered to 3 dogs who presented neurological sequels resulting from the canine distemper. Cases: Dog 1. A 9-month-old male mixed breed; Dog 2. A 6-month-old male Shih Tzu. Dog 3. A 6-month-old bitch mixed breed. All animals were referred for neurological care because presented neurological damages after distemper involvement. Only the Dog 2 was vaccinated to CD. Dog 1 (mixed male) had severe myoclonus, lack of proprioception, decreased of muscle tonus and paralysis in both pelvic limbs, associated with a marked thoracolumbar kyphosis. Dog 2 (a puppy Shih Tzu male) presented myoclonus in PL, proprioceptive loss in thoracic and pelvic limbs, absence of withdrawal reflex in thoracic and pelvic limbs, decrease in muscle tonus in pelvic limb and increase in thoracic limb. Dog 3 (adult unneutered bitch) presented intense myoclonus, absence of proprioception, decrease in muscle tonus and paresis of pelvic limb. All patients were treated with antiparkinsonian medication (levodopa 250 mg associated with carbidopa 25 mg) with following dosages: Dog 1 received a commercially available tablet, orally once a day for 30 days, while Dogs 2 and 3 had doses calculated by extrapolation allometric. For the Dog 2 it was prescribed 0.25 mg of levodopa and 0.025 mg of carbidopa daily for 30 days. Dog 3 was treated with 1 mg of levodopa and 0.1 mg of carbidopa patient day for the same period. Thirty days after starting the treatment, the 3 patients were evaluated again, and showed improvement of the motor signs, and the treatment was maintained. At the next return (30 days): Dog 1 showed significant improvement, however, Dog 2 started to present epileptic seizures and nystagmus that were treated with levetiracetam, while the Dog 3 not returned. As Dog 1 had a better prognosis, treatment was maintained for 1 year, with the frequency being changed from 24 h x 24 h to 48 h x 48 h after 30 days and 72x72 h after another 30 days. Unfortunately, Dog 2 had a worsening of epileptic condition and died, while Dog 3 died by road-kill. Discussion: The cases reported are uncommon, because not exist information about the use of antiparksonian to treatment of neurological damages occasioned by canine distemper. Although there are emerging therapies, such as the use of mesenchymal stem cells, that can reduce these sequels, the access is still restricted to a few professionals. Thus, the use of medications for demyelinating diseases, as antiparkinsonian, may be an alternative. In fact, the three reported patients showed recovery of the motor and sensorial damages observed, which corroborates with the possibility of a new treatment using antiparkinsonian or other drugs to demyelinating diseases. Keywords: antiparkinsonian, distemper viroses, neurology, dogs. Descritores: antiparkinsoniano, cinomose, neurologia, cães.